Specifity of strength training and test protocols in ski jumping - Pozzo, R.; Canclini, A.; Strobl, J.; Baroni, G. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
The use of free barbell loads is a common method in strength testing. Nevertheless, under these conditions, the maximal power output of the legs is strongly influenced by the dynamical stiffness of the spine. Force and power output of leg extension measured on leg-press dynamometers give an accurate profile of leg performance profile (Hahn 2005). The aim of this study is to verify the difference between two kind of testing protocols for strength and power of the legs under increasing loads performed by skijumpers.